Tumor budding and depth of invasion can be used as prognostic risk factors in determining treatment plan for early stage oral squamous cell carcinoma - Mohan, Kaduganoor Ramakrishnan; Sharief, Rahamathulla Mudassar; C., Rahila (International Journal of Research in Medical Sciences, 2019)
Background: The grading of oral squamous cell carcinoma can be useful along with TNM staging in determining treatment plan. The aim is to evaluate the prognostic value of histopathological grading of oral squamous cell carcinoma and to find its importance in setting appropriate treatment plan. Methods: The study includes 60 oral squamous cell carcinoma cases surgically operated during January 2012 to December 2018. From the archival paraffin blocks and available resected specimens of each case, the histological parameters used in Bryne’s invasive grading system and Almangush BD model were evaluated and compared to their prognosis. Results: The parameters used in BD model-tumor budding and depth of invasion were found to be statistically significant with prognosis of the disease. Except for nuclear polymorphism, the parameters used in Bryne’s invasive front grading system do not correlate with prognosis. Conclusion: Based on the prognostic significance, tumor budding ≥5 buds in the invasive front area and depth of invasion ≥4mm can be used as risk factors in prospective clinical trials by considering them in early stage disparity cases for multimodality treatment approach and elective neck dissection.